Estudo da viabilidade técnica de um trocador de calor casco e tubo com alterações em sua geometria interna - Walter, Luiz Augusto Balzan (2018)
Heat exchangers are equipments that take advantage of the temperature difference of two fluids and serve as boundaries for the transfer of energy through the heat. Among the various models on the market, the shell and tube is the most widely used in the industry in general. It is robust, easy to operate, is resistant to high temperatures and pressures, in addition to its hygienization occur in a simple way and damaged components are easily replaced. Because of this large use of the shell and tube heat exchanger, researchers are looking to find ways to improve their operation through algorithms and simulations. This work aims to increase the thermal exchange area of a shell and tube by adding undulations in the pipes and consequently increase the effectiveness of the heat exchanger. To perform the modeling, an equation survey was made and Matlab® software was used to write the code. As a result, the project proved to be feasible in relation to the increase in the area available for exchange since it increased the heat exchange by up to 1000W.